Trajetórias acadêmicas de pessoas com deficiência no ensino superior brasileiro - Morgado, Liz Amaral Saraiva (2017)
The research had as main theme the access and permanence of students with disabilities in Higher Education Institutions (HEI) as well as the investigation of how the students' academic trajectory and the impact within the institutions occur. The objects were to analyze the educational trajectory of people with disabilities in Brazilian Higher Education; to describe the conditions of access and permanence of persons with disabilities in Brazilian Higher Education; to indicate, within the academic trajectory, the conflicts in the political construction of accessibility; to verify the restructurings caused by the policies related to the access of people with disabilities in Brazilian Higher Education. The study was of qualitative character. The data were collected through semi-structured interviews. Participated in the research nine subjects who were contacted and selected previously. The data were analyzed and divided into three categories: i) access and permanence in Higher Education with four subcategories: selective process, affirmative actions, sports and supports; ii) Restructuring of Higher Education Institutions with the presence of people with disabilities and iii) accessibility groups. The results of the research demonstrated a great necessity to ensure adequate educational care for the access and permanence of students with disabilities at the University. The institution needs to promote more directive policies for the inclusion of the person with disabilities in the academic environment.